Control System of Multitasking Interactions between Society 5.0 and Industry 5.0: A Conceptual Introduction & Its Applications. (February 2020) - Elim, H I; Zhai, G
Abstract: The basic concept of control system of multitasking interactions between Society 5.0 and Industry 5.0 (MISI-5.5) is presented in order to have a critical thinking or expert thinking for facing a current complex life of man on earth. The integration of internet of things (IoT), big data (BD), and artificial intelligence (AI) associated with living (L), mobility (M), and working (W) of a person on earth was derived based on their unseparated links in the language of a couple three differential equation particularly from the wisdom extracted according to the knowledge and understanding of current sophisticated nanotechnology system. Finally, the relationship between control system and its feedback can be easily formulated in a matrix system so that the whole big picture of such multitasking interactions is obviously understandable. The impacts of this work are applicable to various actions and reactions in many different fields such as herbal medicines, airplanes, robots, birds, animals, or human being because of its fundamental contribution.